Manager psychopathy, trait activation, and job performance: a multi-source study. Issue 4 (4th July 2018) - Blickle, Gerhard; Schütte, Nora; Genau, Hanna A.
ABSTRACT: Individuals high in psychopathy are often portrayed as more likely to display antisocial behaviour in the workplace and to demonstrate lower job performance. Current research on the impact of trait psychopathy in the workplace is characterized by divergent findings of moderate versus weak effects. We aim to address two potential causes for these discrepant results: mono-source bias and the failure to consider the situational factors that can activate psychopathy. In addition, we used the triarchic model of psychopathy, which incorporates the meanness dimension, a conceptualization of predatory orientation. Our multi-source design disconfirmed concerns that the effects of psychopathy are merely based on mono-source bias. More specifically, we found that the predatory orientation of managers high in psychopathy and especially high in the trait of meanness was behaviourally activated by high levels of ascendency prospects and prospects for income increases. High psychopathy, mediated by consideration towards subordinates and moderated by high ascendency prospects and high prospects for income increases, was associated with low supervisory job performance ratings. Implications and limitations of our findings and directions for future research are discussed.